Psychoanalysis in Arun Joshi’s The Foreigner and The Strange Case of Billy Biswas: A Critical Study - Kaushal Trivedi (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2020)
The current challenges and topics addressed by Indian novelists working in English in the include identity crisis, alienated self, socio-cultural forces, desire for identity, and battle for equality. Arun Joshi, unlike his forefathers, does not create fiction for the sake of amusement or social or political advocacy. He uses novel writing as a vehicle for exploring the contemporary man's position, notably the motivations behind his acts and the psychological impact of those actions. He discusses the challenges of westernised Indians who have lost their spiritual root and are plagued by cynicism, alienation from society, intellectual questions, and religious crises. He notices the disintegration of ancient values, which results in an insane world. The researcher, in this paper, attempts to apply psychoanalytical techniques to Arun Joshi's two novels- The Foreigner and The Strange Case of Billy Biswas by using the frameworks of most appropriate psychological theories to analyse eastern yet primarily westernised characters. His characters stress the unconscious' effect on the aware. The author delves into his subjects' conscious, subconscious, and unconscious mental processes.